PALAYA a low-cost modified push-type manual rice transplanter with seedling container and floats for efficient planting to alleviate the plight of farmers who own more or less 0.5 to 4 hectares of land - Gandingco, Ma. Jacqueline C. (College of Fine Arts, University of the Philippines Diliman, 2017)
The Philippines is an agricultural country. However, less and less people are getting involved in agriculture as it is no longer seen a profitable employment. Rice is the staple food of Filipino but food is not the only allocation of rice; through time, there has been a shortage of it. Traditionally, after the seedlings are manually removed from the nurseries, shaken, washed, bunched, and separated, they are transplanted in the puddled soil by hand which required 8-12 laborers to transplant one acre. But what is really happening? Four things: acute shortage of manual labor, human stress, drudgery, and health risks. I believe a transplanter is one alternative. I designed a push-type manual transplanter with seedling container (a container for seedlings and a farmer's accessories) and floats (for smoother and easier maneuverability on wet soil). My research will benefit rice farmers who own a small piece of land it may, in the long run, also benefit farmers from other provinces.